Artificial intelligence as an information analysis process: A systematic literature review - Fakhlina, Resty Jayanti; Rahmi, Lailatur; Zalmi, Fadhila Nurul Husna; Fadzil, Ghazali Mohamed; Yudisman, Septevan Nanda; Hutagalung, Mawaddah Warahma; Trinova, Regita (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Technological developments in the field of Library and Information Science (LIS) are increasingly rapid, along with advances in information and communication technology (ICT). One of the most recent innovations highlighted is the use of Artificial Intelligence (AI), such as ChatGPT, which is gaining recognition for its potential to support information analysis. Purpose: This research aims to explore and analyze previous research related to the implementation of AI as part of technological developments in the LIS field, using the Systematic Literature Review (SLR) method. Method: The method used is Systematic Literature Review (SLR) using Publish or Perish (keywords: ‘library,’ ‘ICT,’ ‘AI’). Initial 48 articles (2019-2023) screened to 38. Data analyzed using Mendeley and visualized with VOSviewer. Findings: The study showed a significant upward trend in the number of studies on the application of AI in the LIS field over the period. AI is considered an effective tool in supporting information analysis. Researchers emphasized the importance of human intervention in the final analysis; results generated by AIs require further verification and analysis to ensure their validity and relevance in a more specific research context. Conclusion: AI plays a key role in the development of LIS and ICT. Library management must implement strategies such as AI integration, competency development, user AI literacy, and ethical policy development.